Sorghum (Sorghum bicolor L.) yield response to rainwater harvesting practices in the semi-arid farming environments of Zimbabwe: a meta-analysis - Kubiku, Friday N.M.; Mandumbu, Ronald; Nyamangara, Justice; Nyamadzawo, George (Heliyon, 2022)
Rainwater harvesting practices are increasingly gaining recognition as viable adaptation strategies to overcome rainfall variability caused by climate change in semi-arid regions of Zimbabwe. A meta-analysis was conducted to provide a comprehensive quantitative synthesis of biophysical conditions (rainfall, soil texture, N fertility, mulch) under which basins, rippers, and tied ridges affected sorghum yields in semi-arid areas of Zimbabwe. Rainfall amount (<600 mm, 600–1000 mm), soil texture (20 % clay, 20–35 % clay), mulch (basin þ mulch, ripper þ mulch, tied ridges þ mulch), and fertility (0–30 kg N/ha, 30–100 kg N/ha) were used to evaluate the response of sorghum grain yield to rainwater harvesting practices. Grain yield response was compared to the control (conventional practice) using the weighted mean yield difference approach. The results showed comparable sorghum grain yields in all the rainwater harvesting practices across the biophysical conditions, except under rainfall and soil textural classes. Tied ridges had a significant (p < 0.05) negative sorghum grain yield response ( 0.25 t/ha) under <600 mm of rainfall, while ripper planting resulted in a substantial negative grain yield response ( 0.32 t/ha) under 600–1000 mm of rainfall. Ripper planting reduced grain yield significantly (p < 0.05) ( 1.06 t/ha) in soils with 20–35% clay. The results suggest that basins, rippers, and tied ridges did not improve sorghum grain yield across all agronomic conditions.
Keywords: Rainwater harvesting; Rainwater harvesting technologies; Sorghum production